Enactment of social workers bill: Enchancing competent social work practice - Chan, Soak Fong (2014)
In the last five decades, Malaysia has undergone rapid economic, educational and technological growth as well as dramatic social cultural changes. Meanwhile, the nation is also increasingly challenged by multi-dimensional and high-risk social problems.With the growth in human service consumers and providers, there will be increasing risk of harm towards clients that problems may be exacerbated, or not addressed at all if service providers do not have the professional competency to respond appropriately to their needs.In this regard, qualified competent social workers are profoundly needed.Social work has been practiced over 68 years in Malaysia. Compared to other countries that have already recognized social work profession through legislation, in Malaysia, there is still a lack of professional body to monitor and regulate social work practice as well as education and training towards achieving professional standards.A regulation is needed to ensure professional accountability, ethics and competencies of social workers who provide services to the community most in need. Hence, the Social Workers Bill is enacted as a fundamental strategy in the Government’s initiative to introduce a new era of professionalism in social work.It aims to regulate the qualifications as well as strengthening the competence and professionalism of social workers through legislation to ensure quality of services and professionalism in social work.By regulating the professional competency of social workers, the Bill will strengthen the capacity and quality of overall social welfare services, especially for the care, safety and protection of the vulnerable in Malaysia.